2021
DOI: 10.3892/ijmm.2021.4920
|View full text |Cite
|
Sign up to set email alerts
|

FXII regulates the formation of deep vein thrombosis via the PI3K/AKT signaling pathway in mice

Abstract: deep vein thrombosis (dVT) is a common peripheral vascular disease, which may result in pulmonary embolism and is accompanied by endothelial injury. However, the pathogenesis of dVT remains unclear. coagulation factor XII (FXII), as an important coagulation factor, has been reported to be closely associated with thrombosis. However, the association between FXII protein and dVT formation is not yet fully understood. The present study examined the effects of FXII protein on dVT formation and aimed to reveal the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The IVC tissue was dehydrated in gradient ethanol and embedded in paraffin. After deparaffinization and rehydration, the sections (4 mm) were examined by TUNEL apoptosis detection kit (Alexa Fluor 640; Shanghai Yeasen Biotechnology Co., Ltd., Shanghai, China) (20).…”
Section: Transferase-mediated Deoxyuridine Triphosphate-biotin Nick E...mentioning
confidence: 99%
“…The IVC tissue was dehydrated in gradient ethanol and embedded in paraffin. After deparaffinization and rehydration, the sections (4 mm) were examined by TUNEL apoptosis detection kit (Alexa Fluor 640; Shanghai Yeasen Biotechnology Co., Ltd., Shanghai, China) (20).…”
Section: Transferase-mediated Deoxyuridine Triphosphate-biotin Nick E...mentioning
confidence: 99%
“…The process of thrombosis is usually accompanied by the transformation of acute inflammation to chronic inflammation, and inflammation is closely related to DVT (42, 43). Recent studies have found that inflammation factors like IL-6, IL-1, and TNF-a were elevated in both DVT patients and mice (44,45) and activated platelets and coagulation system, which further promoted thrombosis (46,47). Neutrophils are essential in the development of thrombotic inflammation in DVT.…”
Section: Discussionmentioning
confidence: 99%
“…The malondialdehyde (MDA) levels were examined by enzyme-linked immunosorbent assay according to a published research protocol (21) . After complete cell lysis, the supernatant was mixed with the working solution of the kit and heated for 45 min.…”
Section: Oxidative Stress Level Detectionmentioning
confidence: 99%